Liquid scintillator for 2D dosimetry for high-energy photon beams - Pönisch, Falk (American Association of Physicists in Medicine, 2009)
Complex radiation therapy techniques require dosimetric verification of treatment planning and delivery. The authors investigated a liquid scintillator (LS) system for application for real-time high-energy photon beam dosimetry. The system was comprised of a transparent acrylic tank filled with liquid scintillating material, an opaque outer tank, and a CCD camera. A series of images was acquired when the tank with liquid scintillator was irradiated with a 6 MV photon beam, and the light data measured with the CCD camera were filtered to correct for scattering of the optical light inside the liquid scintillator. Depth-dose and lateral profiles as well as two-dimensional (2D) dose distributions were found to agree with results from the treatment planning system. Further, the corrected light output was found to be linear with dose, dose rate independent, and is robust for single or multiple acquisitions. The short time needed for image acquisition and processing could make this system ideal for fast verification of the beam characteristics of the treatment machine. This new detector system shows a potential usefulness of the LS for 2D QA.